2010
DOI: 10.1002/pssa.201026428
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐level composite nanostructures based on the arrays of vertically aligned carbon nanotubes and planar graphite layers

Abstract: New composite nanostructures based on two allotropic forms of carbon, the arrays of vertically aligned carbon nanotubes (CNTs) and planar graphite layers (PGL) located at the top of the arrays, so‐called “CNT–PGL nanostacks”, have been synthesized by the injection CVD method using xylene/ferrocene solution. Two‐ and three‐level nanostacks were demonstrated. The possible scenario of the growth mechanism of these nanostructures is proposed, that is, each level of the nanostack grows by the simultaneous PGL and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…The samples were cut from different directions, and we did not find any difference. From another report and the growth process, we think that the interfacial layer is composited of graphite layers. To investigate the growth process of this structure, we reduced the time of S4 to 10 min.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…The samples were cut from different directions, and we did not find any difference. From another report and the growth process, we think that the interfacial layer is composited of graphite layers. To investigate the growth process of this structure, we reduced the time of S4 to 10 min.…”
Section: Resultsmentioning
confidence: 94%
“…Layered CNTs prepared by CVD have also been reported . In particular, Labunov et al reported that graphite layers can be synthesized between layered CNTs by the injection CVD method. Their work is very important to the study of CNT‐graphene structures.…”
Section: Introductionmentioning
confidence: 99%
“…The latest obtained hybrid nanostructures based on these two allotropes of carbon are nanostructures composed of an array of vertically aligned CNTs and a planar graphene multi-layer (PGL) located at the top of the CNT array (CNT-PGL nanostructure). One-level [2][3][4] and multi-level nanostructures (designated as CNT-PGL nanostacks) [5,6] have been created. Such structures possess a number of new specific properties and open a way to the creation of essentially new functional devices in the area of nanoelectronics, nanophotonics and nanoelectromechanics.…”
Section: Introductionmentioning
confidence: 99%
“…In order to produce such CNT-PGL nanostacks, exfoliated graphene oxide flakes were reduced to graphene after the adhesion of catalyst particles for the growth of CNTs. In other cases, one-level [2][3][4], as well as multi-level nanostructures [5], was synthesised by the CVD method with the localised [2] or floating [3][4][5] catalyst. However, so far, only the general description of the creation process of CNT-PGL nanostructures and their characteristics are presented.…”
Section: Introductionmentioning
confidence: 99%
“…They have consequently been proposed for use as key elements in applications such as nanometer-scale devices [1], biomedical-devices [2], and composite materials [3]. In these CNT-based applications, combined loads are widely expected to occur on the CNTs.…”
mentioning
confidence: 99%